Carnosine and Beta-Alanine Supplementation in Human Medicine: Narrative Review and Critical Assessment - Cesak, Ondrej; Vostalova, Jitka; Vidlar, Ales; Bastlova, Petra; Student, Vladimir (Nutrients, 2023)
The dipeptide carnosine is a physiologically important molecule in the human body, commonly found in skeletal muscle and brain tissue. Beta-alanine is a limiting precursor of carnosine and is among the most used sports supplements for improving athletic performance. However, carnosine, its metabolite N-acetylcarnosine, and the synthetic derivative zinc-L-carnosine have recently been gaining popularity as supplements in human medicine. These molecules have a wide range of effects-principally with anti-inflammatory, antioxidant, antiglycation, anticarbonylation, calcium-regulatory, immunomodulatory and chelating properties. This review discusses results from recent studies focusing on the impact of this supplementation in several areas of human medicine. We queried PubMed, Web of Science, the National Library of Medicine and the Cochrane Library, employing a search strategy using database-specific keywords. Evidence showed that the supplementation had a beneficial impact in the prevention of sarcopenia, the preservation of cognitive abilities and the improvement of neurodegenerative disorders. Furthermore, the improvement of diabetes mellitus parameters and symptoms of oral mucositis was seen, as well as the regression of esophagitis and taste disorders after chemotherapy, the protection of the gastrointestinal mucosa and the support of Helicobacter pylori eradication treatment. However, in the areas of senile cataracts, cardiovascular disease, schizophrenia and autistic disorders, the results are inconclusive.
Keywords: Dietary Supplements; kosterní svaly; dipeptidy; karnosin; lidé; Carnosine; Antioxidants; Dipeptides; beta-Alanine; potravní doplňky; Muscle, Skeletal; antioxidancia; beta-alanin; Humans